Simulasi Deployment Jaringan Sensor Nirkabel Berdasarkan Algoritma Particle Swarm Optimization - Zawiyah Saharuna; Widyawan; Sujoko Sumaryonjo (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2012)
Deployment is one of several important issues in Wireless Sensor Network (WSN). During WSN deployment, the connectivity between each sensor nodes must be considered carefully to create reliable communication. In this research, we propose a WSN deployment tool based on Particle Swarm Optimization (PSO) algorithm with connectivity of the wireless to be our concern. Implementation of the PSO algorithm is focused to optimize received power of each sensor node based on its position in the 2D space. Therefore, every sensor node in the network will be able to reach its best position and improves the network connectivity. The deployment simulation results with various transmit power (e.g. -25 dB, -28 dB, -31 dB, -34 dB, -37 dB, -40 dB, -43 dB, and -46 dB) are successfully form a network with well maintained connectivity. After 100 times of simulation, the average of convergence is reached at iteration 29.